Predicting September sea ice: Ensemble skill of the SEARCH Sea Ice Outlook 2008–2013. Issue 7 (1st April 2014) - Stroeve, Julienne; Hamilton, Lawrence C.; Bitz, Cecilia M.; Blanchard‐Wrigglesworth, Edward
Abstract: Since 2008, the Study of Environmental Arctic Change Sea Ice Outlook has solicited predictions of September sea‐ice extent from the Arctic research community. Individuals and teams employ a variety of modeling, statistical, and heuristic approaches to make these predictions. Viewed as monthly ensembles each with one or two dozen individual predictions, they display a bimodal pattern of success. In years when observed ice extent is near its trend, the median predictions tend to be accurate. In years when the observed extent is anomalous, the median and most individual predictions are less accurate. Statistical analysis suggests that year‐to‐year variability, rather than methods, dominate the variation in ensemble prediction success. Furthermore, ensemble predictions do not improve as the season evolves. We consider the role of initial ice, atmosphere and ocean conditions, and summer storms and weather in contributing to the challenge of sea‐ice prediction. Key Points: Analysis of Sea Ice Outlook contributions 2008‐2013 shows bimodal success Years when observations depart from trend are hard to predict despite preconditioning Yearly conditions dominate variations in ensemble prediction success